30.8k views
1 vote
4 (3q-2) = 4q + 2q


Show your work

2 Answers

5 votes

Answer:

Hi there! The answer is q=4/3.

Explanation:

First—Distrubute the 4 on each side of 3q-2. You should get 12q-8 on the left side of the equation.

Second— Combine like terms. You should see the 4q+2q obviously. Since they have the same letters, they should be combined Into 6q.

as a result you should have 12q-8 on the left side and 6q on the right side.

Switch 6q’s place with -8. But make sure you change the signs of negative and positives as you switch.

Now you should have 12q-6q=8.

Combine like terms again which will be 12q-6q Which will become 6q.

Now you should have 6q=8. divide 6 to both sides of the equation.

Since 6/6 = 1, there should be no coefficients stuck on the q.

when 8 is divided by 6, you should get 8/6.

WAIT YOU ARE NOT FINISHED YET!! YOU HAVE ONE MORE STEP AND YOU WILL HAVE ANSWER.

simplify 8/6 top and bottom divided by 2 each, then you should have 4/3.

Comment if you are confused!! :)

User Shevach
by
5.5k points
3 votes

Answer:

8/6 or 1 1/3

Explanation:

Step 1:

4 ( 3q - 2 ) = 4q + 2q Equation

Step 2:

12q - 8 = 4q + 2q Multiply

Step 3:

12q - 8 = 6q Combine Like Terms

Step 4:

12q = 6q + 8 Add 8 on both sides

Step 5:

6q = 8 Subtract 6q on both sides

Step 6:

q = 8 ÷ 6 Divide

Answer:

q = 8/6 or 1 1/3

Hope This Helps :)

User Samuel Robert
by
4.4k points